Penerapan Asas Pacta Sunt Servanda Pada Perjanjian Lisan Antara Nelayan Pemilik Bagang Ikan Teri (PENJUAL) Dengan Pembeli Di Desa Tanggetada, Kecamatan Tanggetada - Yeni Haerani; Patma Sari; Irsan Rahman, Ld; Dedihasriadi Dedihasriadi; Basrawi Basrawi; Faisal Herisetiawan Jafar; Ruhul Amin (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This study aims to analyze the Application of the Pacta Sunt Servanda Principle in Oral Agreements Between Fishermen Who Have Anchovy Bagang (sellers) and Buyers in Tanggetada Village, Tanggetada District. The formulation of the problem posed, How is the application of the principles of the agreement to the verbal agreement between fishermen who own anchovy bagang and buyers in the village of Tanggetada, Tanggetada sub-district and What are the legal consequences of not applying the principles of the agreement to an oral agreement between fishermen who own anchovy bagang and buyers, Type the study used the Normative-Empirical research method where the results showed that the application of the pacta sunt servanda principle from the buyer was not fulfilled where in the agreement between the seller and the buyer had agreed on a price of 500,000. but the buyer only paid 400,000. so that the buyer violates the agreement that has been made. Legitimate legal consequences based on Article 1388 of the Civil Code, namely all agreements made legally apply as laws to those who make them, an agreement cannot be withdrawn other than by agreement of both parties or for reasons stated by law. , and an agreement must be implemented in good faith. The consequences for buyers who violate the principle of pacta sunt servanda are giving compensation as stipulated in article 1246. an agreement cannot be withdrawn other than by agreement of both parties or for reasons stated by law, and an agreement must be carried out in good faith. The consequences for buyers who violate the principle of pacta sunt servanda are giving compensation as stipulated in article 1246. an agreement cannot be withdrawn other than by agreement of both parties or for reasons stated by law, and an agreement must be carried out in good faith. The consequences for buyers who violate the principle of pacta sunt servanda are giving compensation as stipulated in article 1246.